Development of real time experimental system for investigating photochromic response to UV irradiation - Nadir, Najiah; Wahid, Zaharah; Shafie, Amir Akramin; Abdul Muthalif, Asan Gani; Abdul Malek, Mohamad Zahid; Nik Abdul Aziz, Nik Mohd Azmi; Zainuddin, Mat Tarmizi; Mohamed Islam , Noor Zalikha (IOP Publishing, 2013)
Photochemistry is a field of chemistry that deals with the chemical effects of light such as ultraviolet (UV), visible (Vis) or infrared (IR) radiation. Among many types of photochromic molecules, particular attentions have been given on spiropyrans because of their potential applications in industrial fields. Spiropyrans have the ability to change their chemical structure after exposed to a certain appropriate wavelength of light. However, spiropyrans are very sensitive dyes. For these reasons, an UV irradiation chamber was developed to control the surrounding environment which governs the external light intervention during photochromic work and when direct absorption measurement was performed. The chamber was then exploited to investigate the substituent effect on the absorption spectra of Benzo Indolino Pyrano Spiran (BIPS) dyes, 6-nitro BIPS and 8-ethoxy-6-nitro BIPS. Thus, our results suggest that the developed chamber was successfully utilized for photochromic system since it can protect the dyes from environmental intervention.